Riuen les meduses: cos i desig a la poesia de Carmelina SánchezCutillas i Maria-Mercè Marçal. - VICEDO, NOÈLIA DÍAZ (Scripta, 2021)
This article explores for the first time the continuities between the poetry of Maria-Mercè Marçal (1952-1998) and Carmelina Sánchez-Cutillas (1921-2009). Particularly, it focuses upon the poetic works published during their lifetime, collected in the volumes Abolished Language (1973-1988) (1989) by Marçal and Poetic Works (1997) by Sánchez-Cutillas. Despite their different socio-historical conditions, in this article I analyse how their vital particular experiences as female subjects become the cornerstone of their writing and how the position of their body interacts with language, consequently challenging their inherited socio-cultural significations. In order to discuss my points, I draw upon the parameters developed by the theoretical framework of écriture féminine developed by philosophers Hélène Cixous and Luce Irigaray.